Familial intracranial haemorrhage due to factor V deficiency. - Wadia, R S (1992)
Strokes may occur with a large number of genetic disorders. Natowicz and Kelley have reviewed the single gene disorders capable of causing familial haemorrhagic strokes. These may be classified into four groups: a) hereditary disorders affecting clotting factors or platelets; b) hereditary disease producing vascular anomaly; c) hereditary disease causing hypertension and d) miscellaneous group including neurofibromatosis, sickle cell disease and tuberous sclerosis.